CHARATERIZATION ON OPTICAL PROPERTIES OF CARBON NANODOTS FROM SCREW PINE LEAVES FOR COPPER ION DETECTION - Ngara, Zakarias Seba; Lende, Damaris Natalia; Johannes, Albert Zicko; Bukit, Minsyharil (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2025)
Here, we fabricate, characterize and synthesize the highly fluorescent carbon nanodots (C-dots) from screw pine leaves (SPL). The objectives of this research are to fabricate C-dots from SPL using the carbonization method which is followed by sonication, centrifugation and filtering processes, to charactrize the optical properties of the as-prepared C-dots, and to applied these C-dots as sensor for detection of copper (Cu2+) ions. The optical properties of the C-dots can be characterized from their absorption (Abs), photoluminescence (PL), and Fourier Transform infrared (FTIR) spectra. Whereas the application of the as-produced C-dots as sensor for Cu2+ ions detection can be investigated by the quenching of PL intensity of C-dots after coordination with Cu2+ ions. The analysis of Abs, PL, and FTIR spectra demonstrated the formation of C-dots from SPL in ethanol solutiion. These C-dots have an absorption peak at 276 nm corresponding to the π→π* transition and PL peak at 401 nm corresponding to their blue fluorescence. Fortunately, the interaction between the as-prepared C–dots and Cu2+ ions displayed the PL quenching of the C-dots with the LOD value as low as 2.85 μM. Based on these results, these C-dots exhibited the sensing system for Cu2+ ions detection